1997
DOI: 10.1111/j.1151-2916.1997.tb02984.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Size and Test Configuration on the Wear Behavior of Alumina

Abstract: is not a general rule, however, and that this conclusion depends The effects of grain size on the tribological behavior of on the test configuration, a parameter which has been rarely alumina were investigated. Alumina specimens with three different grain sizes, namely 4, 8, and 14 m, were used as studied. pins and disks in a flat-pin wear test in which the apparent contact area was maintained constant during the test. In II. Experimental Procedure contradiction with previously published reports obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The average wear rate values determined for the monolithic alumina material (2.3 × 10 −9 g/m N and 1.2 × 10 −7 mm 3 /m N, Table 2) agree with those reported for alumina materials with similar grain size under various wear configurations [17][18][19] taking into account that wear is a test system-configuration property and that large data dispersion has been reported in pin on disk tests performed inter and within laboratories. Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The average wear rate values determined for the monolithic alumina material (2.3 × 10 −9 g/m N and 1.2 × 10 −7 mm 3 /m N, Table 2) agree with those reported for alumina materials with similar grain size under various wear configurations [17][18][19] taking into account that wear is a test system-configuration property and that large data dispersion has been reported in pin on disk tests performed inter and within laboratories. Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Substantial differences exist for the wear of alumina against alumina, depending on the test conditions. Except for the single results of Xiong et al, 11 (Fig. 6(f)), the wear of polycrystalline alumina generally increases with an increase of the grain size.…”
Section: (1) Dependence Of Friction and Wear On Grain Sizementioning
confidence: 83%
“…13,14 However, this phenomenon appears to be highly dependent on test configuration, as is indicated by other data showing a decrease in specific wear rate with increasing grain size. 15 Choosing a reactive sintering route for metal-ceramic composites has the advantage that the materials can be sintered pressureless to high densities. It has been shown that materials with 50 vol.% Cr can be sintered to a density of 95% T.D.…”
Section: Introductionmentioning
confidence: 99%